JURIDICAL REVIEW OF INVESTIGATION PROCESS AND OBSTACLES IN THE POLICE FORCE FOR THE SETTLEMENT OF CRIMINAL ACTS OF DOMESTIC VIOLENCE - Mieke Anggraeni Dewi; Ervina Dwi Indriati; Widiati Dwi Winarni (Jurnal Meta-Yuridis, 2023)
Criminal acts of domestic violence (KDRT) have recently sprung up and there has been a special law that regulates it. The law that regulates domestic violence is the Law of the Republic of Indonesia Number 23 of 2004 concerning the Elimination of Domestic Violence, known as UUPK. The purpose of this study is to find out and explain the process of investigating and resolving cases of domestic violence at the police, based on observations at the Demak Resort Police, and to find out the obstacles faced by the police in resolving cases of crimes of domestic violence based on observations. at the Demak Resort Police. The research method used is normative juridical research. The results of research on domestic violence at the Demak Police Station show the following: The forms of domestic violence crimes that are reported to the Police in general are domestic violence which are classified as "Physical Violence" and "Neglect Violence". namely Economic Factors, Jealousy or infidelity Factors, and Alcohol Factors.